1996
DOI: 10.1080/03079459608419176
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity ofRiemerella anatipestiferbroth culture bacterin and cell‐free culture filtrate in ducks

Abstract: Strains belonging to Riemerella anatipestifer serotype 1 are responsible for most of the major disease outbreaks caused by this organism in ducks in Thailand. Therefore, the immunogenicity induced by a broth culture bacterin prepared from a local strain (1081) of this serotype was studied in ducks and a protective index (PI) was derived. The inactivated vaccine contained the equivalent of 5 X 10(9) colony-forming units of bacteria per 0.5-ml dose. A single subcutaneous inoculation of the broth culture bacterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…To date, 21 RA serotypes have been classified (Bisgaard, 1982;Sandhu & Leister, 1991;Loh et al, 1992;Pathanasophon et al, 1995Pathanasophon et al, , 2002 and several serologically unclassified strains have been reported, which may further increase the number of serotypes in the near future (Kö hler et al, 1997;Metzner et al, 2008). Cross-protection between the different serotypes is poor (Sandhu, 1979(Sandhu, , 1991Pathanasophon et al, 1996). Thus identification of the predominant RA serotypes circulating in a certain area is necessary for the choice of appropriate RA vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 21 RA serotypes have been classified (Bisgaard, 1982;Sandhu & Leister, 1991;Loh et al, 1992;Pathanasophon et al, 1995Pathanasophon et al, , 2002 and several serologically unclassified strains have been reported, which may further increase the number of serotypes in the near future (Kö hler et al, 1997;Metzner et al, 2008). Cross-protection between the different serotypes is poor (Sandhu, 1979(Sandhu, , 1991Pathanasophon et al, 1996). Thus identification of the predominant RA serotypes circulating in a certain area is necessary for the choice of appropriate RA vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…An OmpA protein was characterized for its possible use in serodetection of R. anatipestifer infection (28). Inactivated bacterins and live vaccines have successfully conferred protection against homologous strains or serotypes of R. anatipestifer but were unable to protect against heterologous serotype exposure (20,22).…”
mentioning
confidence: 99%
“…3,20,21 RAspeci¯c OmpA has also been proposed as an identi¯ca-tion target. 5,14 Our study performed PCR ampli¯cation for both 16S rRNA and OmpA genes, with 15 out of 27 isolates found to be positive for both genes. In terms of PCR products, while the 16S rRNA PCR yielded clear single bands, some OmpA PCR products included double bands (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…13 Inactivated bacterins and live vaccines have successfully conferred protection against homologous strains of RA, but were unable to protect against heterologous serotype exposure. 14,15 An important challenge for veterinary vaccines is to improve cross-serotype protection of RA infection.…”
Section: Introductionmentioning
confidence: 99%